Core-shell of FePt@SiO2-Au magnetic nanoparticles for rapid SERS detection - Hardiansyah, Andri; Chen, An-Yu; Liao, Hung-Liang; Yang, Ming-Chien; Liu, Ting-Yu; Chan, Tzu-Yi; Tsou, Hui-Ming; Kuo, Chih-Yu; Wang, Juen-Kai; Wang, Yuh-Lin (Nanoscale research letters, 2015)
In this study, multifunctional hybrid nanoparticles composed of iron platinum (FePt), silica (SiO 2 ), and gold nanoparticles (AuNPs) had been developed for surface-enhanced Raman scattering (SERS) application. Core-shell structure of SiO 2 and FePt nanoparticles (FePt@SiO 2 ) was fabricated through sol-gel process and then immobilized gold nanoparticles onto the surface of FePt@SiO 2 , which displays huge Raman enhancement effect and magnetic separation capability. The resulting core-shell nanoparticles were subject to evaluation by transmission electron microscopy (TEM), Energy-dispersive X-ray spectroscopy (EDX), zeta potential measurement, and X-ray photoelectron spectroscopy (XPS). TEM observation revealed that the particle size of resultant nanoparticles displayed spherical structure with the size ~30 nm and further proved the successful immobilization of Au onto the surface of FePt@SiO 2 . Zeta potential measurement exhibited the successful reaction between FePt@SiO 2 and AuNPs. The rapid SERS detection and identification of small biomolecules (adenine) and microorganisms (gram-positive bacteria, Staphylococcus aureus ) was conducted through Raman spectroscopy. In summary, the novel core-shell magnetic nanoparticles could be anticipated to apply in the rapid magnetic separation under the external magnetic field due to the core of the FePt superparamagnetic nanoparticles and label-free SERS bio-sensing of biomolecules and bacteria.